Malignant Pleural Effusions: Management Options - McCracken, David J.; Porcel, Jose M.; Rahman, Najib M. (Seminars in Respiratory and Critical Care Medicine, 2018)
Malignant pleural effusion (MPE) represents advanced metastatic malignancy and is associated with poor median survival. Incidence remains high and continues to rise, in part due to changing population demographics. This therefore represents a significant health care burden. Management is predominantly palliative in nature and multiple interventions are available within conventional treatment paradigms, all of which are proven to result in statistically significant patient benefit. This article further explores the methods available in the management of MPE along with the pitfalls, complications, and alternatives. Recent advances within the field are discussed with an exploration of likely future directions, including the role of ultrasound as a prospective predictor and the role of intrapleural fibrinolytic therapy.
Keywords: malignant pleural effusion; talc pleurodesis; indwelling pleural catheter; palliative; care; unexpandable lung; autopleurodesis; thoracic ultrasound